AI-Powered Decision Support Systems in Clinical Nursing Practice: Benefits and Ethical Considerations - Ali Khan; Ahmed Shah; Fatima Malik; Rustiyana Rustiyana (Yayasan Adra Karima Hubbi, 2025)
Rapid advancements in artificial intelligence (AI) have introduced new possibilities for enhancing clinical nursing practice through AI-powered decision support systems (DSS). Increasing patient complexity, rising workloads, and the demand for timely, evidence-based care underscore the need for technological tools that can assist nurses in clinical judgment, risk assessment, and care coordination. This study aims to examine the benefits and ethical considerations associated with the integration of AI-driven DSS in nursing practice, focusing on their impact on clinical efficiency, patient safety, and professional autonomy. A mixed-methods approach was employed, combining a systematic literature review with qualitative thematic analysis of documented nursing experiences across diverse healthcare settings. The findings reveal that AI-powered DSS improve accuracy in clinical decision-making, support early detection of patient deterioration, and reduce cognitive workload for nurses. The results also identify significant ethical challenges, including data privacy concerns, algorithmic bias, reduced human oversight, and potential shifts in nurse patient relational dynamics. The study concludes that while AI-driven DSS offer substantial benefits for clinical nursing practice, their implementation must be guided by robust ethical frameworks, transparent governance, and continuous professional training to ensure responsible and equitable integration.